Antiparticle Contribution in the Cross Ladder Diagram for Bethe-Salpeter Equation in the Light-Front - Sales, J. H. O. [UNESP]; Suzuki, Alfredo Takashi [UNESP] (Springer/plenum Publishers, 2009)
We construct the homogeneous integral equation for the vertex of the bound state in the light front with the kernel approximated to order g(4). We will truncate the hierarchical equations from Green functions to construct dynamical equations for the two boson bound state exchanging interacting intermediate sigma bosons and including pair creation process contributing to the crossed ladder diagram.
Keywords: Bethe-Salpeter equation; Cross-ladder diagram; Light-front